Use of process steam in vapor absorption refrigeration system for cooling and heating applications: An exergy analysis. Issue 1 (31st December 2016) - Anand, S.; Gupta, A.; Anand, Y.; Tyagi, S.K.
Abstract: The exponential increase in cost of conventional fuels shifts the interest toward the use of alternative as well waste energy sources for the operation of refrigeration and air-conditioning units. The present study therefore analyzes the performance of a process steam-operated vapor absorption system for cooling and heating applications using ammonia and water as working fluids based on first and second laws of thermodynamics. A mathematical model has been developed based on exergy analysis to investigate the performance of the system. The different performance parameters such as coefficient of performance (COP) and exergetic efficiency of absorption system for cooling and heating applications are also calculated under different operating conditions. The results obtained show that cooling and heating COP along with second law efficiency (exergy efficiency) increases with the heat source temperature at constant evaporator, condenser, and absorber temperature. Also, COP as well as exergy efficiency increases with an increase in the evaporator temperature at constant generator, condenser, and absorber temperature. The effect of ambient temperature on the exergetic efficiency for cooling and heating applications is also studied. The results obtained from the simulation studies can be used to optimize different components of the system so that the performance can be improved significantly.